SUPERCRITICAL EXTRACTION OF VALUE ADDED CHEMICAL FROM GAHARU - Goh , Wei Min (IRC, 2016)
The essential oil of gaharu had been an interested and big business in many industries. However, the conventional method to extract essential oil which is hydrodistillation has several disadvantages that require long time and high energy consumption with the possibility to losses volatile compounds. There are only a few researches going on to use Supercritical Carbon Dioxide Extraction to extract essential oil from gaharu. Thus, this project focus on Supercritical Carbon Dioxide Extraction method and the optimizing parameters used to extract essential oil are found to be 40MPa, 30oC, with particle size around 2.9mm and extraction time of 1.1 hours.